This I Believe - Moran, Charles McMoran Wilson, Baron (Tufts Archival Research Center, 2006)
Charles Wilson, Sir Winston Churchill's personal physician, recounts how one judged a person during World War I and the importance of altruism and selflessness to determining a person's character.